2007
DOI: 10.2337/db06-1226
|View full text |Cite
|
Sign up to set email alerts
|

Renal Fibrosis and Glomerulosclerosis in a New Mouse Model of Diabetic Nephropathy and Its Regression by Bone Morphogenic Protein-7 and Advanced Glycation End Product Inhibitors

Abstract: Diabetic nephropathy is currently the most common cause of end-stage renal disease (ESRD) in the western world. A mouse model for diabetic nephropathy that encompasses the salient features of this disease in the kidney is not available. Here, we report that CD1 mice, in contrast to inbred C57BL/6 and 129Sv strains, develop ESRD associated with prominent tubulointerstitial nephritis and fibrosis within 3 months and die because of diabetic complications by 6 -7 months after a single injection of streptozotocin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
158
2
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(182 citation statements)
references
References 32 publications
(34 reference statements)
12
158
2
10
Order By: Relevance
“…In this context, it is notable that B6 mice made diabetic by streptozotocin develop variable degrees of tubulointerstitial fibrosis (11,22). In agreement with this result, we find that our eNOS +/+ Akita diabetic mice developed mild tubulointerstitial fibrosis at age 7 mo (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…In this context, it is notable that B6 mice made diabetic by streptozotocin develop variable degrees of tubulointerstitial fibrosis (11,22). In agreement with this result, we find that our eNOS +/+ Akita diabetic mice developed mild tubulointerstitial fibrosis at age 7 mo (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The results demonstrated that strain specific outcomes occur following BSSG exposure that is similar to that following cycad feeding (Wilson et al 2005a). Strain-dependent outcomes have also been noted for streptozotocin treatment (Sugimoto et al 2007), hypoxia (Ward et al 2007), exposure to cannabinoid receptor agonist (Hoffman et al 2005), rinderpest virus (RPV), peste des petits ruminants virus (PPRV) (Galbraith et al 2002), and naloxone (Navarro et al 1991). Although no behavioral deficits were observed in our second in vivo study, there was significant motor neuron loss that was progressive with increasing survival times.…”
Section: Discussionsupporting
confidence: 51%
“…1F and G). As Sugimoto et al (20) elegantly showed, STZ-induced diabetic CD-1 mice exhibit kidney fibrosis, with both glomerulosclerosis and tubulointerstitial fibrosis occurring ;16 weeks after the onset of diabetes ( Supplementary Fig. 1), and at 24 weeks after the initiation of diabetes, diabetic mice exhibited severe fibrosis when compared with control mice (Fig.…”
Section: Discussionmentioning
confidence: 77%